Long-term prognostic significance of early molecular response to imatinib in newly diagnosed chronic myeloid leukemia: an analysis from the International Randomized Study of Interferon and STI571 (IRIS) - Hughes, Timothy P.; Hochhaus, Andreas; Branford, Susan; Müller, Martin Christian; Kaeda, Jaspal S.; Foroni, Letizia; Druker, Brian J.; Guilhot, François; Larson, Richard A.; O'Brien, Stephen G.; Rudoltz, Marc S.; Mone, Manisha; et al. (Blood, 2010)
This study examines the prognostic significance of early molecular response using an expanded dataset in chronic myeloid leukemia patients enrolled in the International Randomized Study of Interferon and STI571 (IRIS). Serial molecular studies demonstrate decreases in BCR-ABL transcripts over time. Analyses of event-free survival (EFS) and time to progression to accelerated phase/blast crisis (AP/BC) at 7 years were based on molecular responses using the international scale (IS) at 6-, 12-, and 18-month landmarks. Patients with BCR-ABL transcripts > 10% at 6 months and > 1% at 12 months had inferior EFS and higher rate of progression to AP/BC compared with all other molecular response groups. Conversely, patients who achieved major molecular response [MMR: BCR-ABL (IS) ≤ 0.1%] by 18 months enjoyed remarkably durable responses, with no progression to AP/BC and 95% EFS at 7 years. The probability of loss of complete cytogenetic response by 7 years was only 3% for patients in MMR at 18 months versus 26% for patients with complete cytogenetic response but not MMR (P < .001). This study shows a strong association between the degree to which BCR-ABL transcript numbers are reduced by therapy and long-term clinical outcome, supporting the use of time-dependent molecular measures to determine optimal response to therapy. This study is registered at www.clinicaltrials.gov as NCT00006343.
Gesehen am 01.06.2023